MORAL VALUES IN AMERICAN FOLKTALES : ‘THE FISHERMAN AND HIS WIFE’ - Siyaswati, Siyaswati (Universitas Negeri Surabaya, 2016)
Lindahl (2004) states that folktales are stories told by people from generation to generation. One of the folktales that the writer discusses is The Fisherman and His Wife. This paper discusses about Moral Values in the ?Fisherman and his Wife?. This folktale was selected as the source of the data in this study because it describes moralities. Several texts were selected for the data to determine the Moral Values in the folktale. The data were collected by reading and analyzing the folktales. There are a number of ways that one might morally educate a child. One can demonstrate various virtues and encourage the child to copy his or her own behavior. Moreover, one might tell folktales with moral lesson in order to encourage favorable behavior. Hopefully this study will give a beneficial to the readers in terms of morality from other cultures to achieve better understanding when dealing with literary texts.